REFRAMES OF INCLUSION BEYOND INSERTION. TECHNOLOGY, DIGITAL INCLUSION AND CITIZENSHIP AND THE ROLE OF THE HISTORY TEACHER IN THE CLASSROOM: REFRAMES OF INCLUSION BEYOND INSERTION. TECHNOLOGY, DIGITAL INCLUSION AND CITIZENSHIP AND THE ROLE OF THE HISTORY TEACHER IN THE CLASSROOM - Tamanini, Paulo Augusto (2019)
This study aims to discuss the contribution of the use of digital technologies in the teaching of History for the digital and social inclusion of students. Based on authors such as Bonilla (2005); Bonilla and Pretto (2011); Bonilla and Oliveira (2011); Lemos (2007; 2011); Castells (2002, 2003, 2005) and Bittencourt (2011), the text addresses the need for the critical insertion of technologies in the teaching of History as a requirement for digital inclusion to take place. This work discusses the different understandings of the term digital inclusion, from the point of view of some authors and governmental programs, as well as the relationship between the concepts of digital inclusion, social inclusion and citizenship, closely intertwined. The research, of a bibliographic nature, aims, finally, to take a citizen perspective of digital inclusion, positioning itself by the defense of a digital inclusion that enables the conscious and authorial use of the technologies by the learner, making the teaching of History more meaningful and appropriate with the demands of the age of knowledge.